Transcriptome and metabolome analyses provide insights into root and root-released organic anion responses to phosphorus deficiency in oat. (11th May 2018) - Wang, Yanliang; Lysøe, Erik; Armarego-Marriott, Tegan; Erban, Alexander; Paruch, Lisa; van Eerde, André; Bock, Ralph; Liu-Clarke, Jihong
Abstract : Transcripts associated with organic anion metabolism and export are increased under P deficiency. Abstract: Roots and root-released organic anions play important roles in uptake of phosphorus (P), an essential macronutrient for food production. Oat, ranking sixth in the world's cereal production, contains valuable nutritional compounds and can withstand poor soil conditions. Our aim was to investigate root transcriptional and metabolic responses of oat grown under P-deficient and P-sufficient conditions. We conducted a hydroponic experiment and measured root morphology and organic anion exudation, and analysed changes in the transcriptome and metabolome. Oat roots showed enhanced citrate and malate exudation after 4 weeks of P deficiency. After 10 d of P deficiency, we identified 9371 differentially expressed transcripts with a 2-fold or greater change ( P <0.05): 48 sequences predicted to be involved in organic anion biosynthesis and efflux were consistently up-regulated; 24 up-regulated transcripts in oat were also found to be up-regulated upon P starvation in rice and wheat under similar conditions. Phosphorylated metabolites (i.e. glucose-6-phosphate, myo -inositol phosphate) were reduced dramatically, while citrate and malate, some sugars and amino acids increased slightly in P-deficient oat roots. Our data are consistent with a strategy of increased organic anion efflux and a shift in primary metabolism in response to P deficiency in oat.